1998
DOI: 10.1021/la980333y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Length on the Protection of Copper by n-Alkanethiols

Abstract: Self-assembled monolayers (SAMs) formed by the adsorption of n-alkanethiols [CH3(CH2) n - 1SH; n = 8, 12, 16, 18, 20, 22, and 29] onto copper provide a flexible method for producing coatings that can protect the underlying metal against corrosion. The ability to tailor the thickness of the coatings at the angstrom-level by choice of adsorbate allows examination of the effect of angstrom-level variations in film thickness on the performance of the SAM as a barrier layer. A combination of infrared (IR) spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
311
3
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(344 citation statements)
references
References 35 publications
23
311
3
7
Order By: Relevance
“…Absorptions in the CH stretch region are >100-fold enhanced over those reported in RAIRS studies (28)(29)(30). The region of Snyder's CH 2 wagging progression (31) in the absorption spectrum can be seen in the expansion.…”
Section: Enhanced Ir Absorption Spectroscopymentioning
confidence: 81%
“…Absorptions in the CH stretch region are >100-fold enhanced over those reported in RAIRS studies (28)(29)(30). The region of Snyder's CH 2 wagging progression (31) in the absorption spectrum can be seen in the expansion.…”
Section: Enhanced Ir Absorption Spectroscopymentioning
confidence: 81%
“…These results revealed that these three n-alkanethiols retarded the anodic oxidation of copper electrodes and longer-chained n-alkanethiols exhibited superior ability to impede corrosion and the anodic oxidation of copper electrodes than shorterchained n-alkanethiols. Laibinis and co-workers (21) have reported that the greater protection provided by the longer-chained n-alkanethiols is probably a result of Figure 8 shows the ECL spectra of various ECL peaks. The maximum emission wavelength of ECL-1, ECL-2 and ECL-3 is at about 425 nm.…”
Section: Effect Of N-alkanethiol Sams On Copper Electrodesmentioning
confidence: 97%
“…SAMs of n-alkanethiols were reported to inhibit the oxidation of copper and provide great protection for the copper electrode (21)(22)(23). In this work, ethanethiol, n-hexanethiol and n-dodecanethiol were self-assembled on the surface of the copper electrodes, respectively, to study their effects on the cyclic voltammetry and ECL behaviours of luminol.…”
Section: Effect Of N-alkanethiol Sams On Copper Electrodesmentioning
confidence: 99%
“…It has also been shown that barrier properties improve with increasing alkanethiol chain length due to an increase in the van der Waals interactions and greater coating thickness [12]. While these observations all suggest that SAM coatings make ideal preservative coatings for fluxless soldering, changes in their structure occur at elevated temperatures, which may reduce their effectiveness.…”
Section: Introductionmentioning
confidence: 99%